MATHEMATICAL MODEL IMPLEMENTATION OF WYE-CONNECTED CURRENT TRANSFORMERS IN DYNAMIC SIMULATION SYSTEM - I. V. Novash; Yu. V. Rumiantsev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents an implementation of a mathematical model for wye-connected current transformers in Simulink-SimPowerSystems environment. TПЛ-10-type current transformer has been taken as an example for calculations that confirm an adequacy of the mathematical model implementation and the possibility of its usage for engineering analysis.